An Evaluation of the Relationships between Psychological Climate and the Styles of Cognitive Preference and Manifest Ideas - Clapp, PhD, Ray; Ruckhtum, PhD, Vorapot (ABAC ODI JOURNAL Vision. Action. Outcome, 2017)
Abstract This study challenges the assumption that the bipolar characteristics of adaption and innovation associated with individual cognitive style preferences directly characterise the content of manifest ideas and in turn the characteristics of organisational change. The findings show psychological climate (in support of the organisational change process) used in this study is significantly related to ideas with adaptive characteristics, but less so to those with innovative characteristics. Furthermore, cognitive style is significantly related to the characteristics of innovative ideas but much less so to adaptive ideas. These two relationships show how the bi-polar characteristics of the Adaptive -Innovative continuum fits with the two characteristics of the manifest ideas where the latter appears as independent. However, while cognitive style and psychological climate have significant relationships with both styles of ideas, climate dominates for ideas with adaptive characteristics, and cognitive style dominates for ideas with innovative characteristics. The lack of a relationship between psychological climate and cognitive style suggests that psychological climate and cognitive style can be considered as independent predictors of adaptive and innovative idea characteristics respectively. Keywords: cognitive style, manifest ideas, psychological climate